"A decision support approach for evaluating liquefied natural gas supply options: Implementation on Greek case study". (10th June 2019) - Strantzali, Eleni; Aravossis, Konstantinos; Livanos, Georgios A.; Nikoloudis, Christos
Abstract: Natural gas as a primary fossil fuel, will grow faster than both oil and coal for the next decades and distinguishes by its lower environmental impact in comparison to other conventional fuels. Natural gas in its liquid form (Liquified Natural Gas), grows seven times faster than pipeline gas. It is, usually, transferred using liquified natural gas carriers stored in cryogenic tanks. A crucial problem in this field is the selection and the evaluation of liquified natural gas export terminals in different countries (liquified natural gas suppliers). The paper attempts to propose a decision support model specialized for this type of problem, adopting green logistics optimization tools as prescribed in circular economy philosophy. A multicriteria analysis, using Promethee II method, is carried out, evaluating all the potential export terminals and studying the case study of Greece. The approach is based on selected criteria in the fields of economic supply, low environmental impact of transportation, satisfaction of technical specifications and the current and future availability of supply. The evaluation procedure includes the ranking of different preference scenarios. The obtained results showed that there are advantageous liquified natural gas supply options for Greece, like Egypt, Algeria, Libya and Norway, with good performances in almost all the criteria. By adopting the proposed methodology, national and commercial decision makers could take advantage to assess future consortiums. Highlights: A methodology is presented to evaluate potential future LNG supply alternatives and the case study concerned Greece. A methodology is presented to evaluate potential future LNG supply alternatives and the case study concerned Greece. A multicriteria analysis has been adopted covering the economic, technical and environmental fields. The selected criteria fall into the most crucial axes for the selection of LNG supplier. The proposed model could be used by decision makers in order to assess future consortiums.